7-(2-Thienyl)-7-Deazaadenosine (AB61), a New Potent Nucleoside Cytostatic with a Complex Mode of Action - Perlíková, Pavla; Rylová, Gabriela; Nauš, Petr; Elbert, Tomáš; Tloušťová, Eva; Bourderioux, Aurelie; Slavětínská, Lenka Poštová; Motyka, Kamil; Doležal, Dalibor; Znojek, Pawel; Nová, Alice; Harvanová, Monika; et al. (Molecular cancer therapeutics, 2016)
7-(2-Thienyl)-7-deazaadenosine (AB61) showed nanomolar cytotoxic activities against various cancer cell lines but only mild (micromolar) activities against normal fibroblasts. The selectivity of AB61 was found to be due to inefficient phosphorylation of AB61 in normal fibroblasts. The phosphorylation of AB61 in the leukemic CCRF-CEM cell line proceeds well and it was shown that AB61 is incorporated into both DNA and RNA, preferentially as a ribonucleotide. It was further confirmed that a triphosphate of AB61 is a substrate for both RNA and DNA polymerases in enzymatic assays. Gene expression analysis suggests that AB61 affects DNA damage pathways and protein translation/folding machinery. Indeed, formation of large 53BP1 foci was observed in nuclei of AB61-treated U2OS-GFP-53BP1 cells indicating DNA damage. Random incorporation of AB61 into RNA blocked its translation in an in vitro assay and reduction of reporter protein expression was also observed in mice after 4-hour treatment with AB61. AB61 also significantly reduced tumor volume in mice bearing SK-OV-3, BT-549, and HT-29 xenografts. The results indicate that AB61 is a promising compound with unique mechanism of action and deserves further development as an anticancer agent. Mol Cancer Ther; 15(5); 922-37. ©2016 AACR.
Keywords: regulace genové exprese u nádorů; Animals; proliferace buněk; DNA Damage; Cell Membrane Permeability; proteosyntéza; Cell Line, Tumor; výsledek terapie; Fibroblasts; Neoplasms; permeabilita buněčné membrány; Gene Expression Regulation, Neoplastic; nádory; DNA; lidé; Survival Analysis; Antineoplastic Agents; Mice; protinádorové látky; messenger RNA; Treatment Outcome; fibroblasty; myši; RNA, Messenger; xenogenní modely - testy protinádorové aktivity; poškození DNA; sbalování proteinů; modely nemocí na zvířatech; Protein Folding; Tubercidin; Protein Biosynthesis; Cell Proliferation; Disease Models, Animal; analýza přežití; Xenograft Model Antitumor Assays; zvířata; tubercidin; nádorové buněčné linie; Humans